A design-aware test code approach for code writing problem in Java programming learning assistant system. (2017) - Zaw, Khin Khin; Funabiki, Nobuo
To advance Java programming educations, we have developed the web-based Java programming learning assistant system (JPLAS) that provides the code writing problem . This problem asks a student to write a source code for a given assignment, where the correctness is verified by running the test code on JUnit . In this paper, we propose a design-aware test code approach for the code writing problem. The design-aware test code tests any important method in the model source code that has the advisable design for the assignment. Thus, by writing a code that can pass it, a student is expected to implement the code with the proper classes/methods in the model code . In evaluations of the proposal, all the students could complete highly qualitative codes for five graph algorithms using the design-aware test codes, where the code quality metrics were measured by metrics plugin for Eclipse .